Gut microbiome modulation mediated by probiotics: Positive impact on growth and health status of Labeo rohita - Ghori, Ifra; Tubassam, Misbah; Ahmad, Tanveer; Zuberi, Amina; Imran, Muhammad (Frontiers in Physiology, 2022)
The current study was targeted to determine the effect of probiotics on the growth, physiology, and gut microbiology of Labeo rohita fingerlings. One hundred and twenty fishes were divided into four dietary groups, each in triplicate for a feeding trial of 90 days. These treatments included T0 (control, basal diet) used as the reference, and three probiotic-supplemented diets represented as Tbc (Bacillus cereus), Tgc (Geotrichum candidum), and Tmc (B. cereus and G. candidum). The probiotics were supplemented at a level of 1 × 109 CFU/g feed. Fishes nurtured on probiotic-added diet showed significantly high physiological improvement (p < 0.05) in terms of growth, feed utilization capacity, hematological profile, and digestive enzymes as compared to control. The fish were subjected to a challenge test after a 90-day feeding trial. The Tmc exhibited maximum fish growth when challenged by Staphylococcus aureus and showed fish survival when compared to control, in which fish mortality was examined. Fish gut microbial composition was modulated by probiotic treatments, especially in Tgc and Tmc as compared to control. The absence of opportunistic pathogens such as Staphylococcus saprophyticus and Sporobolomyces lactosus and detection of lower levels of Trichosporon and Cryptococcus in treated groups indicate the gut modulation driven by applied probiotics. The G. candidum QAUGC01 was retrieved in yeast metagenomics data, which might be due to the production of polyamines by them that facilitated adherence and consequent persistence. In conclusion, it can be suggested that the probiotic-supplemented diet could enhance fish growth and feed efficiency through community modulation and digestive enzymes, which could be a milestone in local aquaculture.